The Important Role of Customer Satisfaction in Sharia Bank in relation to Service Quality and Relational Marketing towards Customer Loyalty - Ari Pranaditya; Harries Arizonia Ismail; Khansa Shabihah (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Purpose - This study aims to examine the effect of service quality on customer loyalty, customers' satisfaction on loyalty and examining how relational marketing affects customer loyalty within the scope of organizations that practice Islamic values in Indonesia.Method - This research is an explanatory research which explain the position of the variables studied and the influence between one variable and another. To process the data in this study using The Structural Equation Modelling (SEM) from the AMOS 20.0 software package.Result - The result of this research shows that service quality, relational marketing and customer satisfaction influences positively and significantly to customer loyalty.Implication - This study implies customers of Bank Syariah Indonesia in Semarang, Central Java Province, Indonesia who have been a customer for more than 1 year.Originality - The paper looks into the relations of service quality on customer loyalty, customers' satisfaction on loyalty and examining how relational marketing affects customer loyalty in Bank Syariah Indonesia in Semarang, Central Java Province, Indonesia in the third year after the merger to seek if the variables have already served well in the company.